DEVELOPMENT OF A MARKETING SYSTEM OF PROCESSED SWEET PATIO PRODUCTS IN HARUM WANGI MSMEs IN BANYUSARI VILLAGE - Burhan Stafrezar (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
UMKM Harum Wangi processes sweet potatoes into various products, including sweet potato brownies and sweet potato cysts. The limited promotion of these products has hindered their widespread recognition among the public, potentially leading to reduced income. This research employs a descriptive method to address this issue. The study involves direct field action and comprises four stages: 1) Observation, 2) Data analysis, 3) Planning, and 4) Implementation. The findings of the marketing research reveal that UMKM Harum Wangi heavily relies on word-of-mouth promotion. To enhance marketing efforts, it is recommended that the business establish a presence on Facebook and Instagram. Leveraging these social media platforms not only offers cost-effective promotional avenues but also extends customer outreach, potentially spanning across Indonesia. Furthermore, for systematic product distribution, establishing sales accounts on e-commerce platforms such as Shopee and Tokopedia is advised. Additionally, creating visually appealing promotional materials like banners and posters can contribute to better brand awareness and public recognition of these MSME products.